If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -1(-6) = 53 Multiply -1 * -6 y + 6 = 53 Reorder the terms: 6 + y = 53 Solving 6 + y = 53 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + y = 53 + -6 Combine like terms: 6 + -6 = 0 0 + y = 53 + -6 y = 53 + -6 Combine like terms: 53 + -6 = 47 y = 47 Simplifying y = 47
| 5x+2d-2x=1 | | 5sinx-4=0 | | u/-9=(-9) | | 2(L+12)=36 | | 3y+2=1-7y | | X-2.4=5.1 | | (p-4)(p+3)=0 | | 16cos^4(x)-12cos^2(x)+1=0 | | 68=t+(-14) | | Z-15=30 | | u-(-14)=19 | | 4*[1-(4-15)/3] | | 6i(4+2i)=equation | | (b-5)(2b-1)=0 | | 5(x+1)-x=4x+5 | | Y(9+y)=y*9+y*y | | -(2n+2n)= | | n+1n-5=0 | | 6i(4+2i)= | | 12x^2+3x-144=0 | | 5x-2(0)=9 | | p-4p+3=0 | | 6x^2+3x-144=0 | | 7(3y-6)=21 | | -10-5x^2=-350 | | k/-9=(-9) | | X*15=4 | | p/(-3)=(-10) | | 5(-4)-2y=9 | | 2x+6x-45=9 | | -2x-32=4(x+5)-4 | | 3x+7=4(2x-2) |